2017
DOI: 10.1111/sji.12507
|View full text |Cite
|
Sign up to set email alerts
|

Thyrotropin Alters T Cell Development in the Thymus in Subclinical Hypothyroidism Mouse Model

Abstract: Subclinical hypothyroidism (SCH) is highly prevalent in the general population and is associated with potential deleterious effects. Although developing T cells express thyroid-stimulating hormone receptor (TSH-R), the changes of T cell development in thymus in SCH have not been fully clarified. SCH mouse model, which is characterized by elevated serum TSH but similar thyroid hormone levels, was used to study the role of TSH in T cell development. Thymus weight of SCH mice increased 18% compared with controls.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…Moreover, patients with hypothyroidism tended to present more frequently kidney dysfunctions, supporting the well-known influence that thyroid hormones have on renal growth, glomerular filtration rate, and renal transport systems [14,15]. When considering the pattern of signs/symptoms at COVID-19 onset, we found that the hypothyroidism group was less likely to present anorexia and low oxygen saturation [16], which is a well-known red flag for COVID-19 greater respiratory involvement and poor prognosis. The latter aspect could be ascribed to a milder cytokine response in patients with thyroid disorders, which may less strongly affect pulmonary function [16,17].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Moreover, patients with hypothyroidism tended to present more frequently kidney dysfunctions, supporting the well-known influence that thyroid hormones have on renal growth, glomerular filtration rate, and renal transport systems [14,15]. When considering the pattern of signs/symptoms at COVID-19 onset, we found that the hypothyroidism group was less likely to present anorexia and low oxygen saturation [16], which is a well-known red flag for COVID-19 greater respiratory involvement and poor prognosis. The latter aspect could be ascribed to a milder cytokine response in patients with thyroid disorders, which may less strongly affect pulmonary function [16,17].…”
Section: Discussionsupporting
confidence: 77%
“…When considering the pattern of signs/symptoms at COVID-19 onset, we found that the hypothyroidism group was less likely to present anorexia and low oxygen saturation [ 16 ], which is a well-known red flag for COVID-19 greater respiratory involvement and poor prognosis. The latter aspect could be ascribed to a milder cytokine response in patients with thyroid disorders, which may less strongly affect pulmonary function [ 16 , 17 ]. Moreover, the lower prevalence of anorexia could be due to the fact that hypothyroidism is often characterized by reduced resting energy expenditure, weight gain, and appetite loss.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have indicated that the ERK signaling pathway is closely related to thymocyte development, and its activation also plays key roles in the development of diverse diseases. [ 41 , 42 ] For example, thyroid-stimulating hormone promotes T cell development and enhances recent thymic output in mice with subclinical hypothyroidism, possibly by protecting thymocytes from apoptosis, which is related to ERK pathway activation. [ 41 ] The ERK signaling pathway is closely related to the formation of ET.…”
Section: Discussionmentioning
confidence: 99%
“…[ 41 , 42 ] For example, thyroid-stimulating hormone promotes T cell development and enhances recent thymic output in mice with subclinical hypothyroidism, possibly by protecting thymocytes from apoptosis, which is related to ERK pathway activation. [ 41 ] The ERK signaling pathway is closely related to the formation of ET. Dual-specificity phosphatase 3 (DUSP3) is a regulator of the innate immune response, and sepsis in DUSP3-deficient mice decreases TNF production and impairs ERK1/2 activation, which enhances the tolerance of the mice to LPS-induced multi-bacterial infection.…”
Section: Discussionmentioning
confidence: 99%
“…T 3 stimulates thymocyte proliferation, which may be the consequence of TSH-mediated increase in thyroid hormones (15). In that light, recent studies have documented a protective effect of TSH on thymocyte apoptosis (16). These and other directional interactions of HPT hormones on immunity have been detailed in several review articles (17, 18).…”
Section: Introductionmentioning
confidence: 99%